PENGELOLAAN MANGROVE BERBASIS PEREMPUAN DAN MODAL SOSIAL - Talitha Wenifrida (Journal Agriculture Sciences, 2019)
Sustainable mangrove management need women and social capital. Not pay attention to women and social capital that exist in society are particularly vulnerable to achieve sustainability. Because women are the social potential in coastal areas, while social capital is a means of control in the management of mangrove. This paper describes the women in the social capital to implement the coastal mangrove management, by analyzing the three-dimensional social ecosystem-based management, the ecological dimension, economic dimension and socio-cultural dimensions of society Bahowo. While the elements of social capital that are used are: trust, values and norms, reciprocity and proactive measures.